IMPROVING STUDENTS’ READING ACHIEVEMENT IN COMPREHENDING NARRATIVE TEXT BY APPLYING THINK PAIR SHARE TECHNIQUE AT SMP SANTO PETRUS MEDAN - Tarigan, Peber Wanta br; Rumapea, Linus; Sembiring, Novalina (Kairos English Language Teaching Journal, 2020)
This research is about improving students’ reading achievement in comprehending narrative texts by apply Think Pair Share technique at SMP Santo Petrus Medan class VIII-4 in academic year 2016/2017. The aim of this research is to improve students’ reading comprehension through Think Pair Share technique. This technique applies by theory Cooper. The objectives of this research are to find out how could Think Pair Share technique improve students’ reading comprehension and how good are the second grade students of SMP Santo Petrus Medan in reading comprehension after having been taught through the Think Pair Share technique. The research was a Classroom Action Research (CAR) which was conducted by applying Think Pair Share technique in teaching reading to the eighth grade students of class VIII-4. It could be seen that there is a significant improvement of students’ reading comprehension. In this research, the data are distinguished into qualitative and quantitative data. The quantitative data are pretest and posttest. The qualitative data consists of field notes, observation and interview. The result of this research shows that the students’ mean score in pretest is 61,20 with 27,28% of the students get score ≥ 70 and in the posttest mean score is 75,51 with 82,75% of the students get score ≤ 70. It shows that there is a significant mean score improvement between pretest and posttest about 55,17%. It is suggested that the teachers use the Think Pair Share technique as alternative technique in teaching reading to the students in Junior High School in order to improve students’ reading comprehension.